Optimization of Inverted All-Inorganic CsPbI₃ and CsPbI₂Br Perovskite Solar Cells by SCAPS-1D Simulation - Pinzón, Carlos (2022)
Perovskite solar cells (PSCs) have substantially increased their power conversion efficiency (PCE) to more than 25% in recent years. However, the instability of these devices is still a strong obstacle for their commercial applications. Recently, all-inorganic PSCs based on CsPbI₃ and CsPbI₂Br as the perovskite layer have shown enhanced long-term stability, which makes them potential candidates for commercialization. Currently, all-inorganic PSCs with inverted p-i-n configuration have not yet reached the high efficiency achieved in the normal n-i-p structure. However, the inverted p-i-n architecture has recently drawn attention of researchers because it is more suitable to prepare tandem solar cells. In this work, a theoretical study of inverted p-i-n all-inorganic PSCs based on CsPbI₃ and CsPbI₂Br as the perovskite layer was carried out using SCAPS-1D software (ver. 3.3.09). The performance of different architectures of PSC was examined and compared by means of numerical simulations using various inorganic materials as the hole transport layer (HTL) and the electron transport layer (ETL). The results reveal that CuI and ZnO are the most suitable as HTL and ETL, respectively. In addition, the performance of the devices was significantly improved by optimizing the hole mobility in CuI as well as the thickness, doping density, and defect density in the absorber layer. Maximum efficiencies of 26.5% and 20.6% were obtained under optimized conditions for the inverted all-inorganic CsPbI₃- and CsPbI₂Br-based PSCs, respectively. These results indicate that further improvements in the performance of such devices are still possible.